Korea's natural wonders : exploring Korea's landscapes - Kim, Amber Hyun Jung (Korea essentials, 2012)
For those living in Seoul, it's easy to conclude that the urban swath of concrete grays and muddy browns is all there is to see in Korea. Yet those who look up can glimpse crests of mountains, seemingly faraway yet thankfully ever-present. Such is Korean nature-never imposing or intimidating, forever patiently waiting for us to take notice. In a way, this book was written in the hope of encouraging more readers to take notice of this subdued, yet spectacular, beauty.